Effects of dimples' arrangement style of rough surface and jet geometry on impinging jet heat transfer - Celik, Nevin (Springer, 2020)
The enhancement of heat transfer from the impinging jets can be reason of tens of parameters. In earlier studies, researchers have done numerous experiments or numerical runs to show the effect of each parameter individually. However, in recent decade some new methodologies, such as Design of Experiment (DoE) and Analysis of Variance (ANOVA) have been used to achieve more comparative parameter analysis and to optimize the number of experiments (or numerical runs). In this study, DoE and ANOVA methods are applied to an experimental impinging jet study. The jet geometry and roughness of impingement plate are the main considered parameters of this study. Beside them, effects of jet-to-surface distance (H) and radial distance (r) on the target surface are analyzed. The data runs are performed for a constant jet Reynolds number 20,000. The Taguchi DoE method is applied to the study in order to design the experiments. Totally 18 experiments are run base on the orthogonal array of L-18 (1(6)) (3(3)), and effects of each design parameter on heat transfer is found out by ANOVA. As a result, it is concluded that, the highest effect on Nusselt number is observed to be the radial distance (88%), while surface roughness has the effect in percentage of 8%. The contribution of jet geometry and jet-to-surface distance are much lower, as being 3% and 1%, respectively.
Keywords: Air-Jet; Design Analysis; Optimization; Impingement; Nozzle; Plate; Sinks